Exploration of low-carbon tea garden development path in Qingshan Village under the "dual carbon" goal - Yan, Zhen; Wang, Zhixin; Chen, Kevin Z. (CGIAR System Organization, 2025)
Against the backdrop of China’s "dual carbon" goals and agricultural green transformation, low-carbon development has become crucial for the high-quality growth of the tea industry. This study explores a feasible low-carbon tea garden development path for Qingshan Village by integrating theoretical research, technical paths, and domestic typical cases.